Kalimat Majemuk Kompleks - Rustiati, Rustiati (Widya Warta, 2013)
The  research  aimed  to describe  (1)  the  patterns  of  Indonesian compound-complex sentences and (2) the meaning relations between one clause and another. The method used was descriptive-qualitative in nature. The data were in the form of written sentences taken from magazines, newspapers, and novels. The data analysis made use of Immediate Constituents Analysis method. The analysis revealed that compound-complex sentences found were of seven patterns: (1) main clause + subclause + subclause (the first pattern comprises five kinds of pattern structure), (2) main clause + main clause + subclause (the second pattern comprises ten kinds of pattern structure), (3) subclause + main clause + main clause (the third pattern comprises nine kinds of pattern structure), (4) subclause + subclause + main cluse (the fourth pattern comprises  two  kinds  of  pattern  structure),  (5)  subcluse  +  main  clause  +  subclause  + subclause (the fifth pattern comprises two kinds of pattern structure), (6) main clause + main clause + subclause + subclause (the sixth pattern comprises three kinds of pattern structure), (7) main clause + main clause + main clause + subclause ( the seventh pattern comprises only one kind of pattern structure). The  meaning  relations  between  one  clause  and  another  were  of  great  variety, depending on the number of clauses. They include (1) addition and time, content, purpose, cause, (2) order and effect, purpose, time, (3) contrast and time, cause, content, (4) contrast and time, cause, content, (5) cause and addition, contrast, (6) content and contrast, addition, (7) purpose/hope and quantification (8) effect and addition, order, (9) condition and choice, addition, (10) concession and addition, (11) restriction and addition, (12) location and addition, (13) addition, purpose, time, cause, condition, non-condition.